The Swedish Version of the eHealth Literacy Questionnaire: Translation, Cultural Adaptation, and Validation Study - Anna E Sjöström; Senada Hajdarevic; Åsa Hörnsten; Ólöf Kristjánsdóttir; Charlotte Castor; Ulf Isaksson (JMIR Publications, 2023)
BackgroundWith the increasing digitalization in health care, an effective instrument is necessary to assess health care consumers' digital competencies-their "eHealth literacy." The 7-scale eHealth Literacy Questionnaire (eHLQ), based on the theoretically robust eHealth Literacy Framework, has shown strong psychometric properties in Denmark and Australia. ObjectiveThe aim of this study was to translate, culturally adapt, and evaluate the psychometric properties of the Swedish version of the eHLQ. MethodsWe followed the Translation Integrity Procedure guidelines to translate and culturally adapt the questionnaire to Swedish using forward and backward translations, review by an expert panel, and cognitive interviewing. The psychometric properties of the Swedish eHLQ were investigated by evaluating its internal consistency (Cronbach α) and a priori-defined factor structure (confirmatory factor analysis). ResultsA total of 236 primary health care patients and parents of hospitalized children were included in the validation analysis. The mean age was 48.5 years, and 129 (55%) were women. All 7 eHLQ scales showed good internal consistency, with the Cronbach α ranging from .82 to .92. Single-factor and 7-factor confirmatory factor analysis showed satisfactory model-fit values. With one exception, all items demonstrated satisfactory loadings on their respective factors. ConclusionsThe Swedish eHLQ demonstrated strong psychometric properties. It has the potential as a useful tool for a variety of purposes, including population surveys, intervention evaluations, and eHealth service implementations.